The Berenstain bears get stage fright - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random, 1986)
Sister Bear worries about her lines in the school play while Brother Bear has no fear. Guess who forgets the lines during the performance?
3 8 10 11 13 19 26 27 30 36
Keywords: Bears -- Fiction; Plays -- Fiction